Analisis Faktor Penyebab Sisa Material pada Proyek Konstruksi Pembangunan UPT BKN (Unit Pelaksana Teknis Badan Kepegawaian Negara) Gorontalo - Muhammad Izul Al Islami; Moh Yusuf Tuloli; Arfan Utiarahman (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Material is one of the most crucial resources in the construction implementation process. However, the occurrence of material waste not only fails to contribute added value to the project scope but can also lead to significant financial losses for the project implementer. This study aims to analyze the factors that cause material waste in the construction project of UPT BKN Gorontalo. The research focuses on several contributing aspects, including design, procurement, handling, implementation, residuals, and other unexpected factors, as well as efforts to minimize material waste. A combination of qualitative and quantitative approaches was employed, involving field surveys, participatory observations, secondary data analysis, and the distribution of questionnaires to contractors and consultants directly involved in the project. The data were then processed using SPSS software to determine the significance and strength of the influence of each variable. The results showed that among the seven variables analyzed, three had a significant effect on material waste: handling (X3), implementation (X4), and other factors (X6). Meanwhile, variables such as design, procurement, residuals, and minimizing material waste did not show a statistically significant effect. Furthermore, the correlation analysis indicated that the variable "other factors" had the strongest relationship with material waste, followed by implementation and handling. The findings of this research are expected to serve as a reference for improving material management in future construction projects to reduce waste and enhance efficiency.